The IMF's Role in Structural Adjustment. - Collier, P; Gunning, J (1999)
In the 1980s conditional lending for structural adjustment in developing countries moved the IMF beyond its role of macroeconomic crisis management. Fund-supported adjustment programmes have often been flawed by a lack of distributional analysis and by poor sequencing of reforms, notably premature financial liberalisation. As a result they have caused avoidable hardship. In addition, the attempt to taper out aid as part of the reform programme leads to avoidable reductions in post-stabilisation growth. An important role for the Fund in post-stabilisation environments is to provide credible signals to private investors.